Relevansi Wajib Belajar 12 Tahun Dengan Kewajiban Belajar Dalam Perspektif Tafsir Dan Hadis Tarbawi - Nur Ali Subhan; Faiz Adittian; Bangkit Rizka Wibowo (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2024)
Abstract; This article aims to analyze the relevance of the government's compulsory education program with the obligation to study from the perspective of tarbawi interpretation and hadith. This research uses a library research method with a qualitative descriptive approach. Data collection was carried out through documentation methods with content analysis techniques to systematically analyze the content of messages and reveal the symbolic meaning implied in primary sources. The research results show that there is a strong relevance between the concept of twelve years of compulsory education in the government program and the obligation to study from the perspective of tarbawi interpretation and hadith. The views of tarbawi interpretations and hadith regarding the concept of the obligation to study in Islam cover all aspects of life with the principle that education is holistic and carried out throughout life; long life education, starting from life in the womb until the end of life; min al-mahdi ila al-lahdi. The dimensions of education include education for happiness in life in the world to safety in the afterlife. Learning and the educational process is a system that must be implemented and must be followed individually and collectively with the aim of strengthening faith and piety. The relevance of the government's twelve-year compulsory education program with the obligation to study in the perspective of tarbawi interpretation and hadith that learning is a basic human need. Substantially, education is a basic need and specifically can only be provided for humans. Learning as a means to improve the quality of life, learning leads to the formation of the whole person and as a strategic vehicle for developing individual potential that is comprehensive and balanced between the inner and outer. Learning as a step to happiness, Islam views one way to obtain world prosperity and happiness in the afterlife through learning and the educational process. Through the learning process of worldly orientation, humans will be guided and directed and spiritualized into a worldly orientation.